Unconventional measurement methods and simulation of aerogel assisted thermoregulation / Mohanapriya Venkataraman ... [et al.] - Venkataraman, Mohanapriya; Militký, Jiří; Mishra, Rajesh; Jandová, Soňa (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Aerogelis characterized as a low density solid, low optical index of refraction, low thermal conductivity, and low speed of sound through materials, high surface area, and low dielectric constant. It has super-insulating characteristics and the heat transfer phenomenon associated with its complex nanoporous structure. Overall, it delivers better thermal performance, improved durability, and faster installation times than the incumbent insulation materials. Due to these advantages, aerogel is used in many industries like manufacturing, oil & gas, automotive, textiles, construction etc., for steam distribution and thermal insulation application. Measurement of thermal properties of aerogel coated material is important to evaluate its usefulness under extreme weather condition. This study was focused on thermal insulation of aerogel coated high performance fibrous materials. Various measurement techniques for different combinations of insulation materials were studied. New methods were explored to measure thermal characteristics at extreme temperatures. Further, a few instruments were to be fabricated to measure and correlate thermal properties at sub-zero temperatures. This study was expected to assist in identifying the optimal thermal measurement technique and the insulation material most suitable for use. The results from the new measurement techniques like PIV and laboratory set-up instrument will be relevant for classification of materials and eventually for quality assessment of all type of insulation materials. Modeling and simulation were used to study the heat transfer through porous aerogel materials. The thermal resistances of samples were found to be directly proportional to its thickness. This may be attributed to decrease in heat losses due to space insulated by fibrous structure and nanoporous aerogel structure. The air permeability was found to be directly proportional to percentage of nanoporosity of the aerogel based fibrous structure. The fabric density and the aerogel present in the fabric have a significant effect on thermal properties of the overall structures. Compared to other materials, the aerogel-based samples were found to have considerably high thermal resistance even at extreme temperatures.